Are a rubber firm's gross revenue, capital expenditure and employment forecasts rational? - an empirical evidence - Habibullah, Muzafar Shah (FAO, 1994)
Business firms have always recognised the need for a view of the future and have used explicit forecasts in their decision making process. Forecasts of economic variables can be obtained directly from survey expectations. This study evaluates the rationality of economic forecasts made by rubber limited companies in a survey published in Business Expectations Survey of Limited Companies. Data on actual and forecast values of gross revenue, capital expenditure and employment are subjected to unbiasedness, and have no serial correlation, efficiency and orthogonality tests for rationality. Findings suggest that forecast values are unbiased predictors of actual values. Moreover, rubber firms in Malaysia were also found to be rational and utilised all available information efficiently when making forecasts